2020
DOI: 10.1002/psp.2378
|View full text |Cite
|
Sign up to set email alerts
|

Regional trajectories in life expectancy and lifespan variation: Persistent inequality in two Nordic welfare states

Abstract: An important dimension of inequality in mortality is regional variation. However, studies that investigate regional mortality patterns within and between national and regional borders are rare. We carry out a comparative study of Finland and Sweden: two welfare states that share many attributes, with one exception being their mortality trajectories. Although Finland has risen rapidly in the global life expectancy rankings, Sweden has lost its historical place among the top 10. Using individual-level register d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In the first paper, Wilson et al (2020) bring a fresh perspective to the study of spatial variation in health and mortality by exploring regional variations in life expectancy (LE) and life span inequality in Sweden and Finland. Using aggregate data on the whole population over a 25‐year period, the study is the first to assess regional inequalities in life expectancy and an innovative new measure of health inequality—lifespan inequality—for these countries, and to compare regional dynamics over time.…”
Section: Applications Of Register‐based Data For Studying Health Ineq...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the first paper, Wilson et al (2020) bring a fresh perspective to the study of spatial variation in health and mortality by exploring regional variations in life expectancy (LE) and life span inequality in Sweden and Finland. Using aggregate data on the whole population over a 25‐year period, the study is the first to assess regional inequalities in life expectancy and an innovative new measure of health inequality—lifespan inequality—for these countries, and to compare regional dynamics over time.…”
Section: Applications Of Register‐based Data For Studying Health Ineq...mentioning
confidence: 99%
“…The first paper in this issue (Wilson et al, 2020) uses data from Finland and Sweden, thus showcasing the comprehensive population register data available from Nordic countries (Sweden, Finland, Denmark and Norway), which provides individual‐level information across multiple dimensions of a person's life course (health, fertility and marriage, residence and SES factors) over several decades. For the majority of European countries without such long‐established population registers, census data linked to death records, health registers and other administrative data (e.g., educational attainment and tax records) provides a representative data source for studying inequalities longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…Substantive spatial variation in all‐cause and cause‐specific mortality has been documented in various contexts, which may represent regional variation in risk factors, regional variation in the composition of the resident population (e.g., in terms of socio‐economic position), and selective internal migration between regions in terms of health status (Keenan et al, 2021; Wilson et al, 2020). In Belgium, substantive spatial variation at both the regional and district level has been documented for all‐cause as well as cause‐specific mortality (Deboosere & Fiszman, 2009; Deboosere & Gadeyne, 2002; Duchene & Thiltgès, 1993; Eggerickx et al, 2018; Grimmeau et al, 2015).…”
Section: Spatial Variation In Mortalitymentioning
confidence: 99%
“…The spatial dimension of this convergence process has hitherto received limited attention, although several arguments suggest that it may be particularly relevant to understand the origin of the mortality advantage. First, several studies have shown that all‐cause mortality is subject to significant, and often persistent, spatial variation within countries (Deboosere & Gadeyne, 2002; Eggerickx et al, 2018; Wilson et al, 2020). Second, specific immigrant groups tend to settle in specific areas (Reniers, 1999), where local conditions may differentially affect the acculturation process and the evolution of mortality risks over time.…”
Section: Introductionmentioning
confidence: 99%
“…In-country inequalities can be indicators of a nation's health, as well as social justice and societal equity [16]. Comparing the length of life in the regions of Sweden and Finland has shown that regional inequalities can exist in high-income countries with high life expectancy and can be extremely persistent [17]. A north-south gradient of life expectancy has been found in England and Wales that was mainly attributable to variations in deprivation status [18].…”
Section: Introductionmentioning
confidence: 99%